Análisis jurídico y doctrinario acerca de la vulneración de derechos y maltrato infantil a niños, niñas y adolescentes en tiempos de pandemia covid-19 en el ecuador en el entorno familiar - Celi Jiménez, Alex Alejandro (2022)
The topic of this degree thesis is: "Legal and Doctrinal Analysis about the violation of rights and child abuse of children and adolescents in times of the Covid-19 pandemic in Ecuador and the family environment", the same that arises from the analysis carried out on the current reality where the mistreatment of children and adolescents is more frequent in these times, just as this type of action could be witnessed more within the context of the Covid-19 pandemic, discovering serious damage to the integrity of the minor as well as the violation of their rights and even death. Every human being has inherent rights, including the right to life, physical integrity, and education, especially children and adolescents, who must be protected because they cannot defend themselves, ending up in the abuse of their rights and integrity. The problem arises when those who should be the protectors are the aggressors. For that reason, during the confinement due to Covid-19, the existence of violence and violation of the rights of minors could be evidenced, depriving them of their main responsibility, which is to study and find themselves at high risk. In this thesis, there were applied many materials and methods which were useful to develop the research. Likewise, there were carried out interviews and surveys with professionals in Law and Psychology, which results were helpful for a better understanding of the reasons why this type of violence occurs. Besides, it was possible to know the causes and consequences that this act generates in the development of the minor. In this manner, to protect the principle of the best interest of the child and the principle of equality.